Inflammatory vaginitis in women on long-term rituximab treatment for autoimmune disorders - Laura Yockey; Sarah Dowst; Reza Zonozi; Noah Huizenga; Patrick Murphy; Karen Laliberte; Jillian Rosenthal; John L. Niles; Caroline M. Mitchell (BMC, 2021)
Abstract Background Consequences of long-term B cell depletion with rituximab are not well understood. We describe inflammatory vaginitis as a potential side effect of long-term rituximab treatment, distinct from previously described vulvovaginal pyoderma gangrenosum. Methods We performed a retrospective analysis of women treated with rituximab for more than 1 year to determine the prevalence and clinical characteristics of vaginitis cases. We conducted a case-control analysis with up to 3 controls for each vaginitis case. Results We identified sixteen inflammatory vaginitis cases. Women with vaginitis were age 23-68 (median 42), primarily being treated for ANCA-associated vasculitis (11/16; 69%). Most reported copious vaginal discharge (100%) and pain with sex (75%). All women with return of circulating B-cells to > 10 cells/mL had complete (5/9) or significant (4/9) improvement in symptoms. In case-control analysis there was no significant difference in length of B-cell depletion, immune parameters, creatinine levels, and history of neutropenia. Conclusion Inflammatory vaginitis is a potential side effect of prolonged continuous B cell depletion with rituximab. More studies are needed to characterize the incidence and etiology of vaginitis among women on long term rituximab therapy and establish a causal relationship.